0.24-0.02(x+2)=-0.05(3-x)

Simple and best practice solution for 0.24-0.02(x+2)=-0.05(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.24-0.02(x+2)=-0.05(3-x) equation:


Simplifying
0.24 + -0.02(x + 2) = -0.05(3 + -1x)

Reorder the terms:
0.24 + -0.02(2 + x) = -0.05(3 + -1x)
0.24 + (2 * -0.02 + x * -0.02) = -0.05(3 + -1x)
0.24 + (-0.04 + -0.02x) = -0.05(3 + -1x)

Combine like terms: 0.24 + -0.04 = 0.2
0.2 + -0.02x = -0.05(3 + -1x)
0.2 + -0.02x = (3 * -0.05 + -1x * -0.05)
0.2 + -0.02x = (-0.15 + 0.05x)

Solving
0.2 + -0.02x = -0.15 + 0.05x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.05x' to each side of the equation.
0.2 + -0.02x + -0.05x = -0.15 + 0.05x + -0.05x

Combine like terms: -0.02x + -0.05x = -0.07x
0.2 + -0.07x = -0.15 + 0.05x + -0.05x

Combine like terms: 0.05x + -0.05x = 0.00
0.2 + -0.07x = -0.15 + 0.00
0.2 + -0.07x = -0.15

Add '-0.2' to each side of the equation.
0.2 + -0.2 + -0.07x = -0.15 + -0.2

Combine like terms: 0.2 + -0.2 = 0.0
0.0 + -0.07x = -0.15 + -0.2
-0.07x = -0.15 + -0.2

Combine like terms: -0.15 + -0.2 = -0.35
-0.07x = -0.35

Divide each side by '-0.07'.
x = 5

Simplifying
x = 5

See similar equations:

| 4x+7x-(6x+8)= | | 58+47=x | | 3x+5=88 | | f(x)=x^4-6x^3+9x^2+6x-10 | | 6n-1+2=4n-7 | | 3x-1=(x+2) | | -6x/-6=6/-6 | | y=10-4/3x | | 2/13x=4 | | -7(x-2)=5(x+2) | | -8+6(5-8x)=166 | | Y+1=6(x+4) | | -7x-12=x | | -5(-5m+7)-8m=-171 | | 7(7n+6)=91 | | 2x^2+5x=5+3x-2x^2 | | N+.11=2n | | 2x+8i=6-(2y)I | | 5x-4=-2+(2x+1) | | -8(x+6)=-112 | | 2(-6n+1)=-94 | | -16=4(a-3) | | 3/8-1/6= | | 6a+4-9a=10-a | | 6x-3y=-72 | | -8(3-8k)=104 | | -2x+7x+30=15 | | 5x-31=4x-10 | | 5x-3q=4x-10 | | 6h+5=-30-h | | 8x^6+5x^3+1=0 | | 1/8x-y=7 |

Equations solver categories